Productivity increase in the manufacturing process under the SMED methodology of Lean Manufacturing (LACCEI, 2024)
Productivity in companies allows to improve operational and quality efficiency. An OEE level below 65% represents low effectiveness and high downtime in the production line. The objective of the article is to increase the productivity levels of a Peruvian microenterprise in the textile and apparel sector, which in its last period obtained an OEE of 31% compared to 75% at the level of international standards. Previous studies applied various solutions to increase productivity levels. The main tools used were Single Minute Exchange of Die (SMED), 5'S and Six sigma of Lean Manufacturing. They managed to increase the productivity index from 0.38 to 1.16 and reduced default processes from 13.12% to 4.23%. They reduced the idle times that generated major delays, transforming them into parallel activities, increasing the production capacity from 4 units per day. However, these solutions were carried out in garment manufacturing micro-companies. The motivation was to be able to carry out the implementation of these tools in the production of hand luggage for the armed forces. For this purpose, the SMED tool was applied in order to eliminate downtime and increase the productivity level to reduce production costs using the least amount of resources. The validation was checked by means of the following case study which obtained as main result an increase in productivity of 51% and an OEE of 86%. It was concluded that the implementation of the SMED tool reduces downtime during the manufacturing process.